2020
DOI: 10.1002/dmrr.3292
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of exenatide and insulin glargine on nonalcoholic fatty liver disease in patients with type 2 diabetes

Abstract: BackgroundThe aim of this study was to investigate the efficacy of exenatide and insulin glargine in patients with newly diagnosed type 2 diabetes mellitus (T2DM) and nonalcoholic fatty liver disease (NAFLD).MethodsWe performed a 24‐week randomized controlled multicentre clinical trial. Seventy‐six patients were randomly assigned 1:1 to receive exenatide or insulin glargine treatment. The endpoints included changes in liver fat content (LFC), visceral adipose tissue (VAT), and subcutaneous adipose tissue (SAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 36 publications
4
78
0
2
Order By: Relevance
“…Similar outcomes have been reported with other GLP-1 agonists [32]. A trial of exenatide versus insulin therapy during eight weeks was associated with greater reversal of liver fat (assessed by ultrasound) [39], and comparable results were recently reported though liver fat was assessed by MRS (magnetic resonance spectroscopy) after 24 weeks treatment [40]. Regarding novel agents, GLP-1/glucose-dependent insulinotropic peptide receptors dual agonist improves NASH and liver regeneration in mice [41] and significantly decreased fibrosis biomarkers and increased adiponectin in patients with T2DM [42].…”
Section: Glp-1 Agonistssupporting
confidence: 72%
See 1 more Smart Citation
“…Similar outcomes have been reported with other GLP-1 agonists [32]. A trial of exenatide versus insulin therapy during eight weeks was associated with greater reversal of liver fat (assessed by ultrasound) [39], and comparable results were recently reported though liver fat was assessed by MRS (magnetic resonance spectroscopy) after 24 weeks treatment [40]. Regarding novel agents, GLP-1/glucose-dependent insulinotropic peptide receptors dual agonist improves NASH and liver regeneration in mice [41] and significantly decreased fibrosis biomarkers and increased adiponectin in patients with T2DM [42].…”
Section: Glp-1 Agonistssupporting
confidence: 72%
“…and NAFLD [40]. DPP-4 inhibitors (sitagliptin, linagliptin, vildagliptin, saxagliptin, teneligliptin, and alogliptin) work by blocking the enzyme that breaks down GLP-1, enhancing the effects and duration of incretins [45].…”
Section: Other Antidiabetic Agentsmentioning
confidence: 99%
“…Figure S1 shows the results of the literature research and study selection. We initially identified 15 potentially relevant RCTs from PubMed, Scopus and ClinicalTrials.Gov databases until to 15 December 2020 [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. After examining the full text of these 15 articles, we excluded four studies [35][36][37][38] because of unsatisfactory inclusion criteria or unsatisfactory outcome measures, as specified in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram.…”
Section: Introductionmentioning
confidence: 99%
“…Only Armstrong et al ( 19 ) used histology biopsy to estimate the severity of MAFLD. We found that methods for non-invasively assessing liver fat content varied by study, with magnetic resonance imaging (MRI) used by Khoo ( 21 , 22 ) and Yan ( 25 ), whereas Zhang and Liu ( 23 , 26 ) used 1 H-MRS. Shao ( 24 ) and Feng ( 20 ) used ultrasound imaging to assess liver fat content and stiffness. In addition, in control group, one study used liraglutide-placebo, one study used gliclazide, two studies used lifestyle modification, three studies used insulin therapy (both intensive insulin therapy or insulin plus metformin) and one study used pioglitazone plus metformin.…”
Section: Resultsmentioning
confidence: 99%